Inclusive pedagogical practices to learn and teach english as a foreign language using electronic media - Gomes, Luiz Fernando; Rodrigues, Beatriz Gama (The ESPecialist, 2011)
In this paper we present and discuss the curricular reformulation occurred in an English Language Teaching course, especially concerning the introduction of new technologies to teach and learn the English language and the results we have been able to notice, relating to the students’ language competences and their development as (future) English teachers. The introduction of new technologies is seen as an indispensable act in a Teaching Education course, as our goal is to provide our students with opportunities to become English teachers who are able to use language in its several and varied manifestations, including written, spoken and virtual texts.